2009
DOI: 10.1063/1.3272953
|View full text |Cite
|
Sign up to set email alerts
|

Long-range collisional energy transfer between charge-transfer (ion-pair) states of I2, induced by H2O and I2(X)

Abstract: Long-range (resonant) energy transfer, between g/u charge-transfer states of molecular iodine [i.e., f0(g) (+)((3)P(0))-->F0(u)(+)((3)P(0)) and E0(g)(+)((3)P(2))-->D0(u) (+)((3)P(2))], induced by collisions with H(2)O and I(2)(X) via multipole coupling, has been observed. Large rate constants, up to 5 x 10(-9) molecules(-1) cm(3) s(-1), for collisional transfer between a range of vibrational levels of the f0(g)(+)((3)P(0)) and F0(u)(+)((3)P(0)) ion-pair states of I(2), by H(2)O, are reported. Some previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…values increase with v E due to increase of the I 2 (E -D) dipole moment 37 and, consequently, probability of the 38 There are differences between rate constant values of the well as Ref. 20 and earlier, especially for v E = 8 (Fig. 4).…”
Section: −−− −− → D) Cinat Rate Constants Presented In This and Previmentioning
confidence: 88%
See 1 more Smart Citation
“…values increase with v E due to increase of the I 2 (E -D) dipole moment 37 and, consequently, probability of the 38 There are differences between rate constant values of the well as Ref. 20 and earlier, especially for v E = 8 (Fig. 4).…”
Section: −−− −− → D) Cinat Rate Constants Presented In This and Previmentioning
confidence: 88%
“…Recently, it was shown that amplified spontaneous emission (ASE; Refs. [16][17][18][19] as well as water impurity 20 − −−− → D) CINAT rate constants. Very recently, the first experimental results for the ungerade D-state CINATs in collisions of molecular iodine with the rare gases Rg = He, Ar, Xe, as well as some preliminary data for the collisions with the I 2 (X) molecule 21 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of part of the broad band around 325 nm, all the emissions above 320 nm in the spectrum are due to E0 g collisional transfer is observed down to 275 nm which is the low-wavelength limit of the emission from the vibrational levels populated (v D = 10−13). Previously, 1 we showed that, under these conditions, the E0 g…”
Section: A Collisional Transfer By H 2 Omentioning
confidence: 99%
“…As it was not possible to record any new spectra with this experimental arrangement, we were restricted to re-examining the original data in the light of our recent study. 1 Consequently, the ideal (v, J) combinations are not always available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation